2017
DOI: 10.1016/j.molcel.2017.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Molecular Mechanisms of Cytokine-Mediated Endocrine Resistance in Human Breast Cancer Cells

Abstract: Summary Human breast cancers that exhibit high proportions of immune cells and elevated levels of proinflammatory cytokines predict poor prognosis. Here, we demonstrate that treatment of human MCF-7 breast cancer cells with pro-inflammatory cytokines results in ERα-dependent activation of gene expression and proliferation, in the absence of ligand or presence of 4OH-tamoxifen (TOT). Cytokine activation of ERα and endocrine resistance is dependent on phosphorylation of ERα at S305 in the hinge domain. Phosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 81 publications
(99 reference statements)
1
91
0
Order By: Relevance
“…A recent study indicates that pro-inflammatory cytokines can induce antiestrogen resistance in MCF-7 cells that is dependent on phosphorylation of ERα at S305 [48]. This phosphorylation, which causes a conformational change in ERα that induces antiestrogen resistance in MCF-7 cells is mediated by IKKB.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicates that pro-inflammatory cytokines can induce antiestrogen resistance in MCF-7 cells that is dependent on phosphorylation of ERα at S305 [48]. This phosphorylation, which causes a conformational change in ERα that induces antiestrogen resistance in MCF-7 cells is mediated by IKKB.…”
Section: Discussionmentioning
confidence: 99%
“…It was Frasor et al who showed that treatment with TNFα and estradiol regulated a set of genes that are clinically relevant because they can distinguish patients with poor response to endocrine treatment (109). In fact, both molecules act together to promote survival of breast cancer cells and progression onto a more aggressive phenotype (110). In this regard, by using global run-on coupled with deep sequencing (GRO-seq) in MCF-7 breast cancer cells, it was demonstrated that TNFα was responsible for exposing latent estrogen receptor binding sites to which estradiol could bind to regulate gene expression.…”
Section: Luminal Breast Cancer Subtypementioning
confidence: 99%
“…Estrogen receptor activity can be switched on or off by other endogenous molecules. Receptor activation may be triggered by intracellular kinases that are activated by diverse signals, including inflammatory cytokines, and induce modifications in the ERα conformation resulting in receptor-mediated genomic (Stellato et al, 2016) (Stender et al, 2017). Moreover, progesterone is known to oppose estrogen actions in the uterus and vagina through the differentiation from proliferative to secretory endometrial cells, production of less potent estrogens and formation of vaginal mucus that hinders sperm survival (Patel et al, 2015).…”
Section: Regualtion Of Receptor Activity As Summarized Inmentioning
confidence: 99%